2019
DOI: 10.2109/jcersj2.19020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of strength based on defect analysis in Al<sub>2</sub>O<sub>3</sub> ceramics via non-destructive and three-dimensional observation using optical coherence tomography

Abstract: Non-destructive analysis is important in terms of improving the reliability of ceramics. In the study, the internal structure of Al 2 O 3 ceramics with artificial pores was observed via optical coherence tomography (OCT). The OCT observation was performed on a surface perpendicular to the tensile surface of the specimen. The spherical pores were successfully observed via OCT. The strength and fracture origin were predicted from the size and position of the observed pores. The lowest predicted strength (which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Based on these results, OCT observation was applied for the nondestructive inspection of the Al 2 O 3 ceramics. 38) Although the details are omitted in this review, the predicted mechanical strength and the morphology and position of the defect as the origin of fractures detected by OCT observation showed good agreements with the strength obtained from a three-point bending test and the SEM observation.…”
Section: Nondestructive Internal Structure Observation 32)34)supporting
confidence: 53%
“…Based on these results, OCT observation was applied for the nondestructive inspection of the Al 2 O 3 ceramics. 38) Although the details are omitted in this review, the predicted mechanical strength and the morphology and position of the defect as the origin of fractures detected by OCT observation showed good agreements with the strength obtained from a three-point bending test and the SEM observation.…”
Section: Nondestructive Internal Structure Observation 32)34)supporting
confidence: 53%
“…In the infrared transmission image, bright spots with sizes of several tens of micrometers were also observed. According to our previous reports, the bright pairs in the OCT images originate from the reflections at the upper and lower surfaces of the pore 23,24 . Although SEM observations of the same positions are not available in this study, it is suggested that there are large pores in the Al 2 O 3 ceramics that grew during sintering.…”
Section: Resultsmentioning
confidence: 56%
“…As described above, swept-source OCT has the necessary features for in situ observation of evolution of the internal structure of green bodies during sintering. Previously, we reported static observations of the internal structure of green bodies and ceramics with artificial defects using swept-source OCT. 23,24 These reports clarify the physical meaning of the raw OCT images of the green body and ceramics by comparing them with images obtained by infrared microscopy, X-ray CT, and ultrasonic microscopy. Other static observations of the internal structure of ceramics using OCT have also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations